2004
DOI: 10.1007/s00431-003-1364-y
|View full text |Cite
|
Sign up to set email alerts
|

Skin manifestations of Kikuchi-Fujimoto disease: case report and review

Abstract: The histopathological findings of cutaneous lesions in KFD are usually similar to those observed in the involved lymph nodes. This report suggests that interface change might be one of the pathological features of the cutaneous manifestations of KFD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“… 1 , 3 , 4 It has been reported that up to 40% of patients with KD have cutaneous eruptions, but no specific skin changes have been described. 4 , 5 , 6 The most common skin manifestations are erythematous macules, papules, plaques, nodules and ulcers, localized on the face, on the upper and lower extremities and on the trunk. 1 , 4 , 5 , 8 In our patient, the first symptom of KD was the appearing of papules and with central suppuration, on her face and on her left hand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 3 , 4 It has been reported that up to 40% of patients with KD have cutaneous eruptions, but no specific skin changes have been described. 4 , 5 , 6 The most common skin manifestations are erythematous macules, papules, plaques, nodules and ulcers, localized on the face, on the upper and lower extremities and on the trunk. 1 , 4 , 5 , 8 In our patient, the first symptom of KD was the appearing of papules and with central suppuration, on her face and on her left hand.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 The most common skin manifestations are erythematous macules, papules, plaques, nodules and ulcers, localized on the face, on the upper and lower extremities and on the trunk. 1 , 4 , 5 , 8 In our patient, the first symptom of KD was the appearing of papules and with central suppuration, on her face and on her left hand. Posteriorly, she also complained of fever and cervical lymphadenopathy and on laboratory examination there was leukopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It mainly affects young people (mean age: 30 years, range: 6-75) 3 , particularly females (male: female ratio of 1:4), 4 with a striking predilection for the cervical nodes 5 (59-98%). 6 Common symptoms are fever (30-50%), 7 malaise (7%), 8 joint pain (7%), 8 chills, weight loss, diarrhoea, nausea, vomiting, sore throat and myalgia. 9,10 Laboratory studies usually reveal leucopenia (25-45.5%) 7 and elevated erythrocyte sedimentation rate (ESR) (40%).…”
Section: Introductionmentioning
confidence: 99%
“…6 Common symptoms are fever (30-50%), 7 malaise (7%), 8 joint pain (7%), 8 chills, weight loss, diarrhoea, nausea, vomiting, sore throat and myalgia. 9,10 Laboratory studies usually reveal leucopenia (25-45.5%) 7 and elevated erythrocyte sedimentation rate (ESR) (40%). 8 Association with ocular manifestations, [11][12][13] arthritis, 14,15,8 liver dysfunction and neurological complications (aseptic meningitis, [16][17][18][19] mononeuritis multiplex 20 or acute cerebellar ataxia 21 ) has also been described.…”
Section: Introductionmentioning
confidence: 99%